Analisis Minat Siswa SDN Wonosari 03 Kota Semarang terhadap Pembelajaran Pendidikan Jasmani Ditinjau dari Maraknya Akses Game Online di Kalangan Pelajar (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this study was to find out how the interest of Wonosari 03 Elementary School students in Semarang City in physical education in terms of increasing access to online games, and also to find out whether there is an effect of playing online games on student interest in learning physical education. research method uses a quantitative approach with descriptive research and associative causal. The research location is in Wonosari 03 Elementary School Semarang City. A sample of 80 students using purposive sampling technique. Collecting data using observation, documentation and questionnaires. With instruments in the form of a questionnaire. Descriptive statistical data analysis percentage and linear regression analysis as data analysis techniques. The calculation using the percentage formula shows that the average student's interest in physical education learning is moderate as many as 38 respondents or 47.5%, theactivity online gaming respondents'is high as many as 41 students or 51.25%. In addition, from the results of simple linear regression analysis, the output of the t test is obtained, which is a significance value of 0.000 (<0.05), which means that there is an effect of playing online games on student interest in learning physical education. This means that Ha is accepted and Ho is rejected.